Hope, Noise, and the Efficiency of Perfect Meritocracy - Luca Beltrametti; Gabriele Cardullo (Institute of Labor Economics (IZA), 2024)
This paper explores the economic effects of imperfect meritocracy in recruitment and career advancement. We compare two career promotion mechanisms: a fully meritocratic system and a "noisy" one, that allows less productive workers to advance. Our model shows that imperfect meritocracy in promotions can boost worker effort through the "hope effect," potentially leading to higher aggregate output and total welfare compared to a strictly meritocratic system. Less skilled workers benefit most under this scenario, while the high skilled are worse off. We conclude that when perfect meritocracy in recruitment is unattainable, it may not be optimal to enforce it in career advancement, offering insights for economic policy.
Keywords: A13; D61; D63; J20; M51; 330; meritocracy; efficiency; recruitment; career advancement